The Masonry timber framed load bearing structure of “Baraccato” system: A numerical model - Salerno,G.; Geremia, F.; Pagano, E.; Zampilli, M; Ruggieri, N.; Stellacci, S. (Historical earthquake-resistant timber framing in the Mediterranean area. Lecture Notes in Civil Engineering, 2016)
In the modern scientific culture, the seismic vulnerability of the architectural heritage is estimated numerically and need mathematical models of the mechanical behaviour of masonry buildings. The constructive system of “baraccate” houses, whose spread andarchitectural and engineering values have been rediscovered recently, still needs mathematical models. In this piece of paper this first effort has been done for a wall from Palazzo Vescovile in Mileto. The comparison between the numerical results and some experimental tests encourages the research efforts to be continued.